Recruitment strategies and lessons learned from a large genetic study of African Americans - Rebecca J. Salowe; Roy Lee; Selam Zenebe-Gete; Marquis Vaughn; Harini V. Gudiseva; Maxwell Pistilli; Ava Kikut; Emily Becker; David W. Collins; Jie He; Sayaka Merriam; Kristen Mulvihill; et al. (Public Library of Science (PLoS), 2022)
Genetic studies must enroll large numbers of participants to obtain adequate statistical power. Data are needed on how researchers can best use limited financial and practical resources to achieve these targets, especially in under-represented populations. This paper provides a retrospective analysis of the recruitment strategies for a large glaucoma genetics study in African Americans. The Primary Open-Angle African American Glaucoma Genetics study enrolled 10,192 African American subjects from the Philadelphia region. Major recruitment approaches included clinic enrollment from University of Pennsylvania (UPenn) sites, clinic enrollment from external sites, sampling of Penn Medicine Biobank (PMBB), and community outreach. We calculated the enrollment yield, cost per subject, and seasonal trends of these approaches. The majority (65%) of subject were enrolled from UPenn sites with an average cost of $133/subject. Over time, monthly case enrollment declined as the pool of eligible subjects was depleted. Expanding to external sites boosted case numbers ($129/subject) and the biobank provided additional controls at low cost ($5/subject), in large part due to the generosity of PMBB providing samples free of cost. Community outreach was costly with low return on enrollment ($978/subject for 220 subjects). Summer months (Jun-Aug) produced the highest recruitment yields (p<0.001). Genetic studies will benefit from a multi-pronged and culturally sensitive recruitment approach. In our experience, the biobank was most cost-effective for control enrollment, while recruitment from clinics (including expansion to new sites) was necessary to recruit fully phenotyped cases.